Ivermectin as a Potential Therapeutic Agent for COVID-19 – case studies - Wijaya, Natalia Sisca; Salim, Sidharta (Cermin Dunia Kedokteran, 2020)
In December 2019, an outbreak of a novel coronavirus (SARS-CoV-2) started in Wuhan, China, and has since become a global threat to human health. To dates, the worldwide response to the COVID-19 outbreak has been largely limited to monitoring/containment. Several types of drug as well as vaccination are still under investigation and clinical trials worldwide. Recently, a study demonstrated ~5000-fold reduction in SARS-CoV-2 virus at 48h in cell culture after a single treatment of ivermectin. A clinical study at University of Utah found that the administration of ivermectin during COVID-19 illness in hospitalized patients is associated with lower mortality and hospital length of stay. We report three confirmed cases of COVID-19 infection with significant improvement clinically and radiologically following treatment with single dose of ivermectin.Pada Desember 2019, wabah yang disebabkan oleh varian baru coronavirus (SARS-CoV-2) dimulai di Wuhan, China, dan saat ini telah menjadi ancaman global bagi kesehatan manusia.Hingga saat ini, respon dunia terhadap wabah COVID-19 masih terbatas pada pemantauan dan isolasi. Di seluruh dunia, beberapa jenis obat dan juga vaksinasi masih menjalani tahap investigasi dan uji klinis. Baru-baru ini, sebuah studi mendemonstrasikan bahwa satu dosis ivermectin mampu mengurangi ~5000-kali kadar SARS-CoV-2 virus dalam 48 jam pada kultur sel. Sebuah uji klinis di Universitas di Utah juga membuktikan bahwa ivermectin terbukti menurunkan angka mortalitas dan juga lama perawatan pasien COVID-19 rawat inap. Kami melaporkan tiga pasien dengan konfirmasi positif COVID-19 yang menunjukkan kemajuan signifikan klinis dan radiologis setelah pengobatan dengan satu dosis ivermectin.